Perilaku pemeliharaan kesehatan gigi remaja di Sekolah Menengah Pertama Negeri 4 Kota Banda Aceh - Sisca Mardeilita (Politeknik Kesehatan Kemenkes Aceh, 2019)
Background: Dental and oral diseases that are suffered by many Indonesian people are dental caries. World Health Organization (WHO) shows the severity of tooth decay (DMF-T index) aged 12 years by 1 (one) tooth. In fact the average caries experience per person (DMF-T index) was 4.85 (high category). One of the prevention of dental caries is by maintaining good and correct dental health. School age is an ideal time to practice the formation of dental and oral health maintenance behaviors..Objectives: This study aims to identify and analyze factors related to dental health behavior in adolescents in the state junior high school 4 in Banda AcehMethods: This type of research is descriptive-analytic with cross sectional approach. The subjects of the study were state junior high school 4 students in Banda Aceh City with a sample of 77 students. Sampling is done by proportionally simple random sampling. Data analysis was carried out by means of univariate, bivariate with chi-square and multivariate with logistic regression.Results and Conclusions: The results of bivariate analysis of variables related to dental health maintenance behaviors are knowledge (p = 0.0001) and attitude (p = 0.024). The logistic regression test results showed that the most influential variable on dental health maintenance behavior in junior high school adolescents in the city of Banda Aceh was knowledge (OR = 2.188), and support the school has no relationship with oral health behavior (p= 0.094). It is recommended that schools and related agencies be able to provide more information and dental health services for adolescents.